Factors influencing investment in s-reits by retail investors. - Lim, Chong Song. (2008)
This study serves to understand investors' trading behaviour and the factors that influence their S-REIT investment. It also explores the trading behaviour of non SREIT investors with prior knowledge and the motivations that will encourage them to invest in S-REIT.